State coercion and control aversion: An internet study in East and West Germany - Katrin Schmelz; Anthony Ziegelmeyer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Do politico-economic systems influence how control affects motivation? We hypothesize that control aversion, meaning crowding-out of intrinsic motivation due to enforcement, has evolved less under the coercive regime of East Germany than under the liberal regime of West Germany. We test this hypothesis in a large-scale internet study with subjects of different generations. The core of our study is a repeated principal-agent game where the principal can control the agent by implementing a minimal effort requirement before the agent chooses an effort costly to her but beneficial to the principal. We find that control aversion is largely stronger among West than among East Germans. The differences are significant and systematic for older Germans of the working population, never for younger Germans of the working population, and only in specific cases for students. Our findings suggest that for East Germans who have been socialized under a coercive regime, the experience of a liberal regime does not make them abandon completely the control-related preferences they have acquired earlier. Differences in reactions to control are vanishing in younger generations who essentially grew up in reunified Germany. More control aversion in the West is driven by more frequent control averse choices, while the strength of reactions to control is similar in both parts of Germany. Surprisingly, intrinsic motivation in the absence of control is very similar among East and West Germans. Our data suggest that control preferences are affected by the nature of the politico-economic system. However, this effect is only short-lived.
Keywords: C81; C90; C91; C93; D02; M52; 330; culture; institutions; intrinsic motivation; online experiment; control aversion; hidden costs of control; hidden benefits of abstaining from control